Multi-Level Governance Collaboration in the Development of Sustainable Tourism in Lebak, Indonesia - Rusito Rusito; Jumanah Jumanah (Publik : (Jurnal Ilmu Administrasi), 2026)
This study aims to analyze the collaboration of Multi-Level Governance (MLG) in the development of sustainable tourism in Lebak Regency, Banten Province. The study employs a qualitative descriptive approach supported by quantitative data obtained through observation, in-depth interviews, and documentation studies. The analysis focuses on three main dimensions within the multi-level governance framework, namely vertical coordination among levels of government, horizontal coordination among regional government agencies, and network governance involving government, tourism business actors, and local communities in the management of tourism destinations. The results of the study indicate that tourism development in Lebak Regency requires policy synergy and collaboration among stakeholders at various levels of government. Vertical coordination is reflected through the alignment of policies between the central, provincial, and local governments, while horizontal coordination is carried out through cross-sector cooperation among regional government agencies. In addition, network governance is reflected in the increasing involvement of tourism business actors and local communities in the tourism sector registered through the Online Single Submission–Risk Based Approach (OSS-RBA) system based on the Indonesian Standard Industrial Classification (KBLI). Therefore, the implementation of multi-level governance plays an important role in supporting sustainable tourism development in Lebak Regency.